Penerapan Teknik Shadowing dalam Kegiatan Menyimak pada Kelas Pusat Bahasa Jepang : Implementation of Shadowing Technique in Listening Activities in Japanese Language Center Class - Wismadewi, I Gusti Agung Galuh; Sutama, I Made; Dewantara, I Putu Mas; Wirahyuni, Kadek (ITScience (Information Technology and Science), 2024)
This study aims to develop innovative Japanese language learning by utilizing shadowing techniques to improve listening skills in Japanese language center class students. Teaching techniques/methods are essential in improving students' motivation to learn, especially in foreign language learning. The shadowing technique, which integrates audio and visual elements, is applied. This study involved a series of experiments involving students as research subjects, which were then evaluated through listening ability tests before and after using the shadowing technique. The study results showed a significant increase in students' listening skills, as measured by aspects of understanding and response speed to the material presented. The results of the increase in Listening Ability were obtained, and the analysis of the average pre-test score of students was 67, while the average post-test score increased to 80. This result shows a significant increase in the values obtained, indicating that shadowing effectively improves students' listening skills. Student feedback: Based on the questionnaire, 86.5% of students reported that the shadowing technique made them more interested and involved in learning. 90% of students agreed that the learning experience with the shadowing technique helped them understand the Japanese language context better. Moreover, Qualitative Interview: From the interview, students stated that they enjoyed activities that involved listening to dialogues in real situations, such as everyday conversations and cultural contexts. These findings are expected to contribute to developing more effective, interesting Japanese language learning methods, increasing interest in learning Japanese, and encouraging the use of technology in language education.